2017
DOI: 10.1002/jmv.24929
|View full text |Cite
|
Sign up to set email alerts
|

Echovirus plays major roles in the natural recombination of Coxsackievirus B3

Abstract: Coxsakievirus B3 (CVB3) is a member of enterovirus B (EVB) group, which can cause serious heart diseases such as viral myocarditis. In order to analyze the evolution of CVB3, we performed a recombination analysis of all viral genomes of enterovirus B, and found that there were 19 putative recombination events that produced CVB3. A total of 11 serotypes were found to be involved in the generation of CVB3 progeny virus. These recombination events involved echovirus, EcoV (which includes EcoV6, EcoV9, EcoV14, Eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…We allocated the worldwide CVB3 variants to twenty-three different evolutionary recombinant lineages based on non-capsid sequences. Several previous studies showed that Chinese CVB3 showed the highest similarity with the parental CVB3 in the P1 region, with the E25 strain in the P2-P3 region, and other strains of CVB3 showed similarity with CVB5 in the P3 region [ 54 , 55 ], which is consistent with our study. However, it remains unclear whether there are substantial differences in recombination frequencies between different EVs such as echoviruses, and whether CVB5 plays a major role in the natural recombination of CVB3.…”
Section: Discussionsupporting
confidence: 92%
“…We allocated the worldwide CVB3 variants to twenty-three different evolutionary recombinant lineages based on non-capsid sequences. Several previous studies showed that Chinese CVB3 showed the highest similarity with the parental CVB3 in the P1 region, with the E25 strain in the P2-P3 region, and other strains of CVB3 showed similarity with CVB5 in the P3 region [ 54 , 55 ], which is consistent with our study. However, it remains unclear whether there are substantial differences in recombination frequencies between different EVs such as echoviruses, and whether CVB5 plays a major role in the natural recombination of CVB3.…”
Section: Discussionsupporting
confidence: 92%
“…The emergence of E30 has been found to exhibit a cyclic pattern with dominance and disappearance of individual recombinants over a period of years [21][22][23][24][25][26][27]. The turnover period for such recombinants has been calculated to be from 1.8 to 5 years [28,29].…”
mentioning
confidence: 99%
“…Various infectious agents contribute to myocarditis, including bacteria, viruses, and parasites to allergens or toxins 4 . Coxsackievirus type B3 (CVB3) is regarded an important cause of viral myocarditis 5 . Achievements in cardiac magnetic resonance imaging and molecular detection of viruses have been made to better understand the mechanisms of viral myocarditis.…”
Section: Introductionmentioning
confidence: 99%